Alternative modification of KBM for solving equations of TE wave spreading in depth of kerr substarte with linear absorbtion - G, Ochirbat; D, Gantulga (Scientific transaction of the National University of Mongolia. Physics, 2022)
K8M method, specialy modified for solving a pair of first order differential equations for TM wave spreading in depth of kerr substrate with linear absorbtion. is used to solve the same problem in the case of TE polarization. Solution, obtained by this alternative modification of KBM. is in full agreement with the solution to Helmgolts’s equation, previously found by another modification of KBM. It is shown that the one of asymptotic series obtained with the method is convergent.